1998
DOI: 10.1093/glycob/8.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Purification of galectin-3 from ovine placenta: Developmentally regulated expression and immunological relevance

Abstract: Galectins, beta-galactoside-binding lectins, are extensively distributed in the animal kingdom and share some basic molecular properties. Galectin-3, a member of this family, is generally associated with differentiation, morphogenesis, and metastasis. In this study, galectin-3 was isolated from ovine placental cotyledons round the middle of the gestation period by lactose extraction followed by affinity chromatography on lactosyl-agarose, and separated from galectin-1 by size exclusion chromatography on a Supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…4,42 On the other hand, redundancy is often built into mechanisms operating in key events during development as a form of fail-safe insurance. 43 Galectins have been implicated in several physiopathological processes requiring carbohydrate recognition, such as cell adhesion, 28 cell growth regulation, 44,45 immunomodulation, 46,47 apoptosis, 34,48,49 inflammation, 50 embryogenesis, 29 reproduction, 51,52 tumor spreading 53,54 and premRNA splicing. 35,55 The precise knowledge of the mechanism of action of galectins is lacking, although their effects are believed to relate to interactions with specific carbohydrate ligands.…”
mentioning
confidence: 99%
“…4,42 On the other hand, redundancy is often built into mechanisms operating in key events during development as a form of fail-safe insurance. 43 Galectins have been implicated in several physiopathological processes requiring carbohydrate recognition, such as cell adhesion, 28 cell growth regulation, 44,45 immunomodulation, 46,47 apoptosis, 34,48,49 inflammation, 50 embryogenesis, 29 reproduction, 51,52 tumor spreading 53,54 and premRNA splicing. 35,55 The precise knowledge of the mechanism of action of galectins is lacking, although their effects are believed to relate to interactions with specific carbohydrate ligands.…”
mentioning
confidence: 99%
“…Future studies should challenge this paradigm in the context of other physiological systems. Consistently, expression of galectins-1 and -3 was found to be differentially regulated during mammalian gestation (43,44). Iglesias et al (44) reported the coexistence of mitogenic galectin-3 and apoptotic galectin-1 (43) in ovine placenta.…”
Section: Galectins-1 and -3: Why A Novel Paradigm?mentioning
confidence: 75%
“…Galectins have been involved in several in vitro physiopathological processes requiring carbohydrate recognition, such as cell adhesion (26), cell growth regulation (38), immunomodulation (39,40), apoptosis (32,41), inflammation (42), embryogenesis (28), reproduction (43,44), tumor spreading (45) and pre-mRNA splicing (25). It should be emphasized that the vast majority of galectin functions have been assigned to galectins-1 and -3.…”
Section: Functions Of Galectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…While galectin-1 has been shown to trigger T cell apoptosis (Perillo et a1.,1995;Rabinovich et al, 1998;Iglesias et al, 1998a), galectin-3 has been shown to stimulate proliferation (Yang et al, 1996;Iglesias et al, 1998b;Inohara et al, 1998). Similarly to members of the Bcl-2 family, galectins-1 and -3 belong to an additional family of proteins with high sequence homologies but opposite effects on cell survival.…”
Section: Galectin-1 Expression In Immune Privileged Sites" a Novel Mementioning
confidence: 99%